Concurrent Improvement in Maize Grain Yield and Nitrogen Use Efficiency by Enhancing Inherent Soil Productivity - Zhigang Wang; Bao-Luo Ma; Yajian Li; Rongfa Li; Qi Jia; Xiaofang Yu; Jiying Sun; Shuping Hu; Julin Gao (Frontiers in Plant Science, 2022)
Quantifying the relationships of maize yield and nitrogen use efficiency (NUE) to inherent soil productivity (ISP) could provide a theoretical basis for implementing strategies that concurrently narrow the yield gap, increase NUE and improve soil quality. A field study under irrigation conditions was conducted at five locations with large differences in ISP (estimated by maize grain yield without using fertilizers) across various ecological regions in Inner Mongolia, China. Our results showed that the changes in maize yield and nitrogen partial factor productivity (PFPN) to ISP followed a linear-plateau model, with a common inflection point. When ISP was below 8.0 t ha-1, maize yield and PFPN were stagnating at a low level, due to a trade-off between the contribution of soil and chemical fertilizers to yield. When ISP exceeded 8.0 t ha-1, the contribution rate of soil to yield stabilized at 80%, resulting in a simultaneous increase in maize yield by 1.2 t ha-1 and PFPN by 4.6 kg kg-1, for increasing ISP at each t ha-1. Our results indicated that while keeping other management strategies unchanged, to increase maize yield and PFPN by 15% or further 30%, it is necessary to increase ISP to 9.3 t ha-1 and 10.4 t ha-1, respectively. In this scenario, N input will be reduced by 33.5% and 47.5%, and apparent N losses will be reduced by 11.7% and 21.5%, respectively. Therefore, enhancing ISP could lead to a simultaneous improvement in yield and NUE as well as strongly support the green development of maize production.